PENGEMBANGAN WISATA BAHARI DENGAN PENDEKATAN EKONOMI KREATIF DI KAWASAN PESISIR PANTAI KABUPATEN BONE BOLANGO - Abdul Wahab Podungge; Muten Nuna; Fiskawati Akuba (Universitas Bina Taruna Gorontalo, 2023)
This reserch aims to find out and describe the factors that determine tourism development, including in terms of infrastructure, accessibility, community participation and tourist attractions. The data analysis used is an interactive model analysis which consists of three components of analysis namely: 1) Data reduction; 2) Data Presentation; 3) Verify Data and Draw Conclusions. The research results show that: 1) the development of basic tourism infrastructure in the coastal area of Bone Bolango is not sufficient. Basic infrastructure facilities including infrastructure, public facilities and tourism facilities do not meet the standards of the tourism development master plan; 2) tourism accessibility in the Bone Bolango coastal area can improve the quality of life of local residents by creating new jobs. Tourism accessibility is also encouraged to pay attention to environmental impacts such as potential damage to coral reefs and underwater waste so that the role of tourism actors is expected to be sensitive and wise in paying attention to the negative impacts of tourism development; 3) community participation in developing tourism destinations in the Bone Bolango coastal area must be carried out using a variety of approaches including information technology to assist marketing, involving community groups who are vulnerable to having no income, and building partnerships with tourism organizations. This is important because the declining community participation is caused by access to information, the style of community consumerism. For this reason, the regional government of Bone Bolango Regency and the village government need to provide regular assistance to the community to encourage sustainable development through the tourism sector; 4) tourist attractions have a significant impact on economic growth and cultural preservation. Encouraging tourist attractions requires careful planning, collaboration between stakeholders, and long-term commitment. With the right efforts, destinations can increase their attractiveness and attract many tourists, thereby contributing to the development of the local creative economy and the sustainability of tourism. By increasing tourist attractions, especially in rural areas, it can increase the income and welfare of rural residents and help prevent excessive urbanization.